Meta-trends in Global Value Chains and Development: Interacting Impacts with COVID-19 in Africa - Carmody, Padraig (My University, 2020)
How will the COVID-19 pandemic affect prospects for foreign investment and development in Africa? In part this depends on its interaction with pre-existing meta-trends in the global economy, such as the rise of China and the coming Fourth Industrial Revolution. It will also depend on the nature of revisions to political settlements in African countries arising from the pandemic. This paper explores these issues through an examination of the direct and indirect economic impacts of the pandemic and their likely interaction with continuing meta-trends in the global economy. In particular it argues that while there may still be an important role for foreign investment in African development, the crisis also creates opportunities for more domestically-focussed investment and production.
ACCEPTED
Keywords: Economic impact; COVID-19; Africa; Investment; Development; International Development; Africa; Development; Employment; Globalization; Policy; Poverty